Toward Gender-Based Inclusive Development: Determinants of Female Labor Force Participation in Indonesia - Kristina Suci Antika; Sitti Retno Faridatussalam (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the effects of early marriage among women, female fertility rates, women’s health, women’s education, and women’s representation in parliament on the female labor force participation rate in Indonesia. A quantitative approach is employed using panel data covering 34 provinces over the 2018–2024 period. The analysis is conducted using a Fixed Effects (FE) model, selected based on the results of the Chow test and the Hausman test. The findings indicate that the female fertility rate has a negative effect on the female labor force participation rate, while women’s health has a positive effect. Early marriage among women, women’s education level, and women’s representation in parliament do not show statistically significant effects. These results suggest that biological and health-related factors play a more substantial role than social and political factors in influencing women’s economic participation. The implications of this study underscore the importance of public policies focused on improving access to reproductive health services and enhancing the overall quality of women’s health in order to promote sustained and inclusive increases in female labor force participation.